Trafficking of women and children for the sex industry in Malaysia / Najwa Hassan and Wan Fazrina Wan Jaffar - Hassan, Najwa; Wan Jaffar, Wan Fazrina (2005)
Due to the absence of Malaysian laws regarding trafficking of foreign labor, we are proposing that specific trafficking law should be introduce in order to curb trafficking of women and children in Malaysia. Trafficking of women and children occurs perhaps because a powerful economy that has arisen around the sale of sex, totally integrated into local and national economies and hugely profitable for industrialist and for states. This research would also include a pilot study that would analyze the perception of the public on the law of trafficking in Malaysia. The result of this analysis would then be used as a template for a larger state or national survey. The study would be conducted through library research.